Prognostic factors affecting postoperative survival of patients with solitary small hepatocellular carcinoma. Issue 1 (December 2016) - Cai, Mu-Yan; Wang, Feng-Wei; Li, Chang-Peng; Yan, Li-Xu; Chen, Jie-Wei; Luo, Rong-Zhen; Yun, Jing-Ping; Zeng, Yi-Xin; Xie, Dan
Abstract Background Small hepatocellular carcinoma (sHCC) is a unique variant of HCC that is characterized by small tumor size (maximum tumor diameter ≤3 cm) and favorable long-term outcomes. The present study aimed to define clinicopathologic factors that predict survival in patients with sHCC. Methods The study population consisted of 335 patients who underwent hepatectomy for solitary sHCC between December 1998 and 2010. Prognostic factors were evaluated using Kaplan–Meier curves and Cox proportional hazard models. Results The 5-year overall survival (OS) and recurrence-free survival (RFS) rates were 77.7% and 59.9%, respectively. Kaplan–Meier curves showed that tumor size and vascular invasion had prognostic significance within this relatively selected cohort (P < 0.05). Multivariate analysis confirmed that increased tumor size and vascular invasion were independent prognostic factors for short OS (hazard ratio [HR] = 2.367, 95% confidence interval [CI] 1.406–3.985; HR = 2.954, 95% CI 1.781–4.900) and RFS (HR = 1.779, 95% CI 1.259–2.514; HR = 1.699, 95% CI 1.165–2.477) in sHCC patients (P < 0.05). Importantly, a proposed prognostic scoring model was derived according to the two variables; tumor size and extent of vascular invasion were significantly associated with OS and RFS in patients with sHCC (P < 0.001). Conclusions Tumor size and vascular invasion are feasible and useful prognostic factors for sHCC. The proposed prognostic model, based on tumor size and vascular invasion, is informative in predicting survival in sHCC patients undergoing hepatectomy.